HUBUNGAN POLA ASU IBU DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI WILAYA KERJA PUSKESMAS DUONO - Lantaka, Jaenet; Retnaningsih, Reny; Alim, Zainal (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, which has an impact on children's physical growth and cognitive development. Mother's parenting style is one of the factors that influences the incidence of stunting in toddlers. This study aims to determine the relationship between maternal parenting patterns and the incidence of stunting in toddlers aged 12-59 months in the Duono Community Health Center working area. This study used a cross-sectional design with a sample of 16 toddlers selected using purposive sampling. Data was collected through interviews using a questionnaire that had been tested for validity and reliability. Data analysis was carried out using the Chi-Square test to determine the relationship between maternal parenting variables and the incidence of stunting. The results of the study show that there is a significant relationship between maternal parenting patterns and the incidence of stunting in toddlers (p < 0.05). Good parenting tends to reduce the risk of stunting in toddlers, while poor parenting increases the risk of stunting. Maternal parenting has an important role in preventing stunting in toddlers. Interventions involving education and increasing mothers' capacity in caring for children need to be improved to reduce stunting rates in the Duono Community Health Center working area.